Current status of the influence of osteoporosis on periodontology and implant dentistry (2020)
Purpose of review This review summarizes recent evidence on the impact of osteoporosis on periodontonlogy and implant dentistry, prevalence of diseases, pathophysiology and treatment outcomes. Recent findings Patients with osteoporosis should be advised about the importance of returning for periodical periodontal maintenance as inadequate oral care may lead to a faster development of periodontitis. There is no definitive information on the development of bisphosphonate-related osteonecrosis of the jaw associated with dental implant therapy. Patients presenting severe periodontitis, undergoing intravenous bisphosphonate therapy (for long-term periods) and submitted to more invasive periodontal/peri-implant surgical procedures (that can promote superior dentoalveolar surgical trauma) might be advised about the possibility of developing bisphosphonate-related osteonecrosis of the jaw following dental therapy. Thus, individualized risk evaluation must be undertaken by both the medical and dental teams prior to any dental treatment. Summary The most recent literature on the impact of osteoporosis on the periodontal and peri-implant tissues was reviewed to emphasize the importance of oral hygiene measures, and the combined medical/dental assessment of importance when osteoporotic patients are in need of dentoalveolar surgical procedures (e.g. tooth extraction and dental implant placement).